1996
DOI: 10.1097/00000542-199610000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flumazenil on Ventilatory Drive during Sedation with Midazolam and Alfentanil

Abstract: Flumazenil effectively reverses the benzodiazepine component of ventilatory depression during combined administration of a benzodiazepine and an opioid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…The slope of the HVR at PetCO 2 of 55 mmHg was decreased by alfentanil and further decreased by midazolam. As expected, the effects of midazolam were completely reversed by the benzodiazepine antagonist flumazenil (1 mg) (232).…”
Section: Benzodiazepine-opioid Combinationsupporting
confidence: 77%
See 2 more Smart Citations
“…The slope of the HVR at PetCO 2 of 55 mmHg was decreased by alfentanil and further decreased by midazolam. As expected, the effects of midazolam were completely reversed by the benzodiazepine antagonist flumazenil (1 mg) (232).…”
Section: Benzodiazepine-opioid Combinationsupporting
confidence: 77%
“…In contrast, Gross et al (232) found that sedative doses of midazolam (repeated doses of 10 μg/kg every minute until loss of response to voice command) added to a low-dose alfentanil infusion (loading infusions plus 0.05 μg/kg/min) further depressed the slope of the CO 2 response (assessed by the steady-state method), that was already depressed and right shifted by the opioid [for details see figure 1 in Gross et al 1996 (232)]. The slope of the HVR at PetCO 2 of 55 mmHg was decreased by alfentanil and further decreased by midazolam.…”
Section: Benzodiazepine-opioid Combinationmentioning
confidence: 89%
See 1 more Smart Citation
“…Consequently, elimination of sedative drugs between day 1 and 3 may be associated with an improvement of respiratory drive and thus EAdi maxSBT values [18]. Flumazenil could have been tested at day 1 in order to quantify EAdi modification [19]. It is also a common observation that surface electromyographic (EMG) amplitude, thus net neural drive to a muscle, increase within days of training using isometric, concentric, or other forms of contraction (more motor units could be recruited or firing faster) [20].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, flumazenil blocks midazolam- (alone or with opiates) induced sedation and respiratory depression [10,11]. In the oversedated individual, flumazenil is administered through intravenous boluses of 0.2–0.5 mg. A common practice is to administer 0.2 mg over 30 s, and increase to 0.3 mg in the absence of response.…”
Section: Reversal Agentsmentioning
confidence: 99%